On a growing central banks accountability for financial stability – macroprudential perspective - Matysek-Jędrych, Anna (Economics and Business Review, 2018)
The aim of this paper is to identify and assess, on a comparative, intra-countrybasis, the existing practices and developments in central bank accountability forfinancial stability, from a new–macroprudential policy–perspective. The paper aims tocontribute to the ongoing debate on institutional arrangements for macroprudentialpolicy. The debate as to whether the combination of monetary policy and financial supervisionwithin one institution is not new. Nevertheless it is far from being resolved.The paper points to the need to establish clear, formal and robust mechanisms of centralbank involvement in the process of executing macroprudential policy, at least asa data collection and analyzing institution.